APLIKASI METODE MCDM-ANALYTIC NETWORK PROCESS (ANP) DAN BALANCED SCORE CARD UNTUK PENGUKURAN KINERJA - Ciptomulyono, Udisubakti; -, Herlina (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
Balanced score card is one of the most popular company performance measurement methods applied in various organisations. This performance measurement sistem was begun with strategic goal determination from finance perpective, customer perspective, internal business process perspective, learning and growth perspective that was derivatived from vision, mision, and company strategy. Then it can be stated Key Performance Indicator (KPI) from each strategic goal. The objectives interrelated was shown at strategy map which needs evaluation with specific integrity technique. The approach that is usually used to find that integrity is AHP (Analytic Hierarchy Process) which pretend a independence link between the performance measurement elements. In fact, each perspective encounter dinamicaly interaction to reach performance. That is why in this research will be suggested the usage of MCDM (Multicriteria-Decision-Making) method Analytic Network Process (ANP) which accomodate perception that strategy perspective elemen that is become organisation has an interrelated effect to one another. The implementation of Performance Measurement System with Balanced Score card method in this industry is become studied got finance perspective can be stated two objectives and two KPI, for customer perspective stated four objectives and four key performance indicators, for internal business process perspective agreed seven objectives and nine key performance indicators. Perspective that is considered important is customer perspective (0.404). the second place is financial perspective (0.241), then internal business process perspective (0.227) and learning and growth perspective (0.128).